MicroRNA MiR-490-5p suppresses pancreatic cancer through regulating epithelial-mesenchymal transition via targeting MAGI2 antisense RNA 3. Issue 2 (1st February 2022) - Xu, Zhenglei; Chen, Zeming; Peng, Minsi; Zhang, Zhuliang; Luo, Weixiang; Shi, Ruiyue; Wang, Lisheng; Hong, Yingcai
ABSTRACT: Pancreatic cancer with about 5% five-year overall survival rate remains a challenge. Invasion and migration of pancreatic cancer cells are the main factors leading to poor prognosis. MicroRNA-490-5p (miR-490-5p) has anti-cancer effects in a variety of tumors, but its role in pancreatic cancer has not been reported. The mRNA expressions of miR-490-5p, MAGI2 antisense RNA 3 (MAGI2-AS3), Matrix metalloproteinase (MMP)2, MMP9, N-cadherin, and E-cadherin were detected by quantitative real-time PCR, while the protein expressions of these genes except miR-490-5p were measured by Western blot analysis. The cell viability, apoptosis, migration and invasion were detected by cell counting kit-8 (CCK-8), apoptosis and transwell assays. MiR-490-5p was abnormally low-expressed in pancreatic cancer, whose down-regulation generated enhanced effects on viability, migration and invasion in pancreatic cancer cells, as well as MAGI2-AS3 expression. MiR-490-5p mimic exerted the opposite effect on cells, which also down-regulated MMP2, MMP9, and N-cadherin protein expressions, while up-regulating E-cadherin protein expression. MAGI2-AS3, which was the targeted binding site of miR-490-5p, promoted viability, migration and invasion, and inhibited apoptosis of cancer cells. More importantly, miR-490-5p played an anti-cancer role in pancreatic cancer by targeting MAGI2-AS3 and regulating epithelial–mesenchymal transition (EMT), which was partially offset by MAGI2-AS3.